Moral development in students with high abilities: State of knowledge from 2002 to 2022 (Research, Society and Development, 2024)
From an early age, children with high abilities show signs of high moral sensitivity. These children, as well as showing an advanced ability to think about abstract ideas such as justice and fairness, can also show superior performance in one or more areas, in isolation or in combination, when compared to students of the same age group, grade and environmental experiences. The general objective was to describe and characterize the state of knowledge on the moral development of students with high abilities. To this end, an integrative literature review was carried out in five electronic databases from 2002 to 2022 (Periódico CAPES, Sage Journal, Eric, Psycinfo and LILACS). The following results were found: i. In total, 14 articles were selected, which indicates a shortage of scientific publications on this subject; ii. quantitative tests for assessing moral development were the most commonly used instruments for assessing moral development in students with high abilities; iii. two theories of moral development were used in studies to explain the moral development of people with high abilities: Piaget's theory and Kohlberg's theory, the latter being cited in international studies and the former in national studies; and iv. the need for educational interventions for the moral development of students with high abilities. The conclusion is that it is necessary to promote scientific research on this subject, as meeting the emotional and educational needs of children with high abilities and the inclusion of this special education group in school depends on the knowledge accumulated by scientific studies.